CAREER ASPIRATIONS AMONG MALAYSIAN YOUTH: A QUALITATIVE STUDY ON THE INFLUENCE OF TIKTOK - Mohamad, Faizul; Ramlan, Muhammad Azril Izuan; Ab Rashid, Faridah Hanem; Ismail, Isma Zuriyya; Azahari, Emir Haqim (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This study examines how TikTok shapes the career aspirations of Malaysian youth, particularly in the context of emerging digital occupations. Although TikTok began as a platform for short-form entertainment, it has evolved into a space where alternative career pathways especially content creation and online influence are prominently visible and increasingly normalised. This visibility appears to influence how young Malaysians evaluate success, stability and future opportunities. Using a qualitative approach, the study draws on in-depth interviews with ten participants to explore how exposure to TikTok content informs young people’s understanding of work, achievement and self-identity. The analysis focuses on the factors that attract youth to digital content creation, the motivations driving their interest and the extent to which the platform reshapes their long-term goals. Emotional and social considerations like the desire for autonomy, creative expression and public recognition also emerged as influential elements. The findings suggest that TikTok plays a meaningful role in shaping contemporary attitudes toward career and aspiration, revealing a widening disconnect between traditional educational trajectories and the possibilities offered by digital platforms. The study highlights the need for parents, educators and policymakers to better recognise the influence of fast-evolving media environments when supporting young people in making informed and realistic future career decisions.